ELECTRONIC GLOSSARY OF LINGUISTIC AND DIDACTIC TERMS AS AN INTERACTIVE TEACHING AID - Eva, MALA; HASKOVA, Alena (Trends in education, 2011)
The authors describe the possibilities of applying an electronic foreign language glossary of linguistic and didactic terms. They mainly concentrate on the interactivity of the programme and the creativity of its users. The possibility of inserting new terms and other examples of their usage is emphasized. The adaptation of concrete linguistic terms is presented as an example in the English language.
Keywords: electronic glossary; linguistic and didactic terms; foreign language equivalents; interactivity; autocreativity.